Strategi Pembelajaran Materi Musik Barat di Kelas XI IPS 1 SMA Negeri 1 Banuhampu - Rudi, Ahmad; Jagar Lumbantoruan (EDUMUSIKA, 2024)
This research aims to find out and describe the Learning Strategy for Western Music Material in Class XI IPS 1 SMA Negeri 1 Banuhampu. This research uses a qualitative approach with descriptive analysis. Researchers act as the main instrument, supported by instruments such as cellphones and stationery. Data collection methods involve literature study, observation, interviews, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions. In learning planning, a lack of consistency was found between Basic Competencies (KD) and learning objectives. At the implementation stage, teachers did not communicate the topics and learning objectives with students. Evaluation is carried out through written tests, with remedial provision to students who have knowledge below the Minimum Completeness Criteria (KKM). The research results show that the discovery learning strategy implemented is less effective, especially in achieving learning objectives as stated in the 2013 curriculum guidelines. Many students still do not understand the characteristics of modal, tonal and atonal music. The discovery of challenges in learning Cultural Arts, it is necessary to improve learning strategies and implementation in order to improve the achievement of learning objectives and student insight of western music material. Therefore, this research illustrates the need to review and improve learning strategies on western music concepts.